Morphology of some Loricate Heterotrophic Species of Flagellate (Choanomonada, Bicosoecida, Jakobida), with Emphasis on Taxonomical Problems of Asexual Protist Species - Tikhonenkov, D.V.; Mazei, Yu.A.; Mylnikov, A.P.; Kireev, A.V. (Вестник зоологии, 2008)
Morphology of the some loricate heterotrophic flagellate species in the natural and clonal populations are investigated. Differential diagnoses and descriptions of species are provided. Some taxonomic problems of loricate heterotrophic flagellates and protists identification are discussed. A new replacement name Salpingoeca skujae Tikhonenkov et Mazey, nom. n. for Salpingoeca urnula Skuja, 1948, nom. praeocc., non Salpingoeca urnula Korshikov, 1926 is proposed. В природных популяциях и клональных культурах исследована морфология некоторых видов гетеротрофных флагеллят, имеющих домики. Приведены дифференциальные диагнозы и описания видов. Обсуждаются некоторые таксономические проблемы идентификации домиковых гетеротрофных жгутиконосцев и других протистов. Представлено новое замещающее название Salpingoeca skujae Tikhonenkov et Mazey, nom. n. для Salpingoeca urnula Skuja, 1948, nom. praeocc., non Salpingoeca urnula Korshikov, 1926.